THE STRATEGIC DRIVING MODEL OF MUANG KLANG SUBDISTRICT MUNICIPALITY IS A LOW CARBON CITY - intarayam, amorntepparit (Academic Journal Phranakhon Rajabhat University, 2020)
The purposes of this study were to study 1) The effectiveness of the strategy driving to be a low carbon city of Muang Klaeng Municipality 2) Factors affecting to the effectiveness of strategy driving the low carbon city of Muang Klaeng Municipality. And 3) The strategic driving model of Muang Klang Subdistrict Municipality is a low carbon city was effective. This research is a combination of quantitative and qualitative research. The sample group is the staff who drive the low carbon city strategy of Muang Klaeng Subdistrict Municipality, Klaeng District, Rayong Province included 44 people. Chairman of the community in Muang Klaeng Municipality included 16 people. A total included 60 people, the key informants were representatives of the Mayor of Muang Klaeng Municipality, Representative Deputy Mayor Muang Klaeng Municipality Permanent Secretary, Muang Klaeng Subdistrict., Acting Director of Public Health and Environment Division Policy and Plan Analyst, Expert Senior Veterinary Officer Municipal officials, Community presidents and Community directors and Community committee included 15 people. Data collection was carried out with a questionnaire and an interview form. Statistics used for data analysis comprised percentage, mean, and standard deviation. A qualitative data analysis was conducted through interpreting and summarizing main points. The results were described elaborately with key point summary presentation. The results of the study showed that 1) The effectiveness of the strategy of driving a low-carbon city of Muang Klang Subdistrict Municipality was at a high level (X̅= 3.71). 2) Factors Affect to the Effectiveness of the Low Carbon City Strategy of Muang Klaeng Subdistrict Municipality is a factor driving the low carbon city strategy in management policy, project management and cooperation had same direction correlation at a high level to the effectiveness of strategic driving as a low carbon city of Muang Klaeng Municipality significant at 0.05. And 3) the strategic driving model of Muang Klang Subdistrict Municipality is an important low-carbon city, is to drive a low carbon city strategy with the authority of the municipality to manage the environment, with factors affecting the effectiveness of the low carbon city strategy, policy is the executive vision, management is to link the work of internal departments, project management is the expertise of personnel, cooperation is a good relationship of personnel and people, with the effectiveness of success and the process of driving a low carbon city strategy of Muang Klaeng Municipality results in People have quality of life and good hygiene. Key words: driving, low-carbon city, effective